2009
DOI: 10.1177/1368430208101347
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Group Composition and Attitudes Towards Diversity on Anticipated Outcomes of Diversity in Groups

Abstract: In two studies, students evaluated group pictures of workgroups of varying ethnic and gender composition with respect to anticipated affective and productive outcomes. The impact of level of diversity, faultlines and individual differences in diversity attitudes on anticipated outcomes were examined. Favorable level effects of diversity were particularly found for groups with weak faultlines and for productive outcomes of diversity. In general, outcomes of cross-categorized groups were anticipated as more favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 73 publications
1
9
0
2
Order By: Relevance
“…Our findings show that there is no one-to-one relationship between objective and perceived diversity, thus speaking to the importance of incorporating both constructs in future research in order to fully understand the effects of diversity on group functioning. The present study also provides relevant insights for research on diversity beliefs and related constructs that have been shown to play an important role in diverse teams (e.g., Ely & Thomas, 2001;Homan et al, 2007aHoman et al, , 2008McKay, Avery, & Morris, 2008;van Knippenberg et al, 2007;Van Oudenhoven-van der Zee et al, 2008). We extend these previous findings by showing why diversity beliefs have beneficial effects on group functioning, that is, we show that diversity beliefs influence how group members construe their diversity.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings show that there is no one-to-one relationship between objective and perceived diversity, thus speaking to the importance of incorporating both constructs in future research in order to fully understand the effects of diversity on group functioning. The present study also provides relevant insights for research on diversity beliefs and related constructs that have been shown to play an important role in diverse teams (e.g., Ely & Thomas, 2001;Homan et al, 2007aHoman et al, , 2008McKay, Avery, & Morris, 2008;van Knippenberg et al, 2007;Van Oudenhoven-van der Zee et al, 2008). We extend these previous findings by showing why diversity beliefs have beneficial effects on group functioning, that is, we show that diversity beliefs influence how group members construe their diversity.…”
Section: Discussionsupporting
confidence: 82%
“…Multiculturalism recognizes and values differences between members from different cultural backgrounds. This diversity perspective is very similar to other concepts such as positive diversity beliefs (van Knippenberg & Haslam, 2003), diversity attitudes (e.g., Sawyerr, Strauss, & Yan, 2005; van Oudenhoven-van der Zee, Paulus, Vos, & Parthasarathy, 2009), or a group’s diversity climate (Luijters, van der Zee, & Otten, 2008), which all refer to the belief that diversity is something valuable. From a social categorisation perspective on group processes (Turner, Hogg, Oakes, Reicher, & Wheterell, 1987), a multicultural ideology proposes a group identity which differentiates between distinct subgroups within a common superordinate identity (Dovidio, Gaertner, & Saguy, 2007).…”
Section: Diversity Perspectives: Multiculturalism and Colorblindnessmentioning
confidence: 57%
“…Though our study is the first to our knowledge that has applied the faultline concept to R&D team performance, the idea of cross‐cutting faultlines has been preceded in the literature. In particular, it was found that ‘cross‐categorized’ groups showed stronger links to performance than groups with strong faultlines (van Oudenhoven‐van der Zee et al., ). Furthermore, Thatcher et al.…”
Section: Discussionmentioning
confidence: 99%